Perjanjian Penempatan Calon Pekerja Migran Berdasarkan Undang-Undang Nomor 18 Tahun 2017 - Sinuraya, Regina Fraulein (Tribuere, 2022)
A migrant worker placement agreement is an agreement for the placement of migrant workers in a destination country. Legal issues about migrant employment, such as insufficient wages, working hours until uncertainty of the country of destination of work. The government provides protection to Indonesian migrant workers before, during and after working in a country. The problem being investigated is the number of agreements on the placement of migrant workers that do not qualify for the validity of the agreement and the lack of implementation of the treaty's basic principles. According to article 6 (f) of Act No. 18 of 2017 on the Protection of Migrant Workers Indonesia regulates the standardization of an Agreement on the Placement of Indonesian Migrant Workers. The aim is for the agreement not to harm either party, for the safety of workers and to reduce the level of violations by the sending company. This research is a normative jurisprudence using secondary data supported by primary data, qualitatively analyzed and deductively concluded. Migrant workers are entitled to the same treatment as other workers. Standardization of the Settlement Agreement is one of the forms of supervision that can prevent the occurrence of legal problems. The employee placement agreement must refer to the terms of validity of the agreement in accordance with Article 1320 of the Code of Civil Procedure Law, which is binding between the migrant employee and the Indonesian migrant worker placement company, has legal force and certainty as a basis for decision-making if something unexpected occurs between both parties. Article 1320 of the Constitution states that for an agreement to be valid, four conditions must be met: the agreement between the parties, the parties claiming to make a agreement, the existence of an object of agreement and a legitimate reason.